Strategi Pengembangan Desa Wisata Melalui Kemampuan Literasi Budaya dan Culture Experience - Rieswansyah, Annisa Fitriana Putri; Rachmawati, Tine Silvana; Winoto, Yunus (Universitas Sebelas Maret Library, 2022)
Tourism activities are one of Indonesia's advantages in the creative economy sector. Villages that have tourism potential and even tourism activities are referred to as tourist villages. In carrying out tourism activities, the management of both the government and the Kelompok Sadar Wisata (Pokdarwis) need to develop strategies to attract many tourists. Local culture is an unavoidable part of tourism activities in tourist villages. This research was conducted with the aim of knowing how the tourism development process in the Desa Wisata Edukasi Cisaat Ciater includes what tourism potential, principles of implementing culture-based tourism activities, public knowledge about culture and cultural tourism, cultural inheritance through culture experience, how cultural literacy plays a role in tourism and activities in Desa Wisata Edukasi Cisaat Ciater. The method used in this research is a qualitative research method with a case study. The results of this research show that Desa Wisata Edukasi Cisaat Ciater does not recognize the term cultural literacy, but in fact what has been implemented is cultural literacy. The selection of cultural tourism is used as an effort to preserve culture, develop local communities, including in terms of the economy, and increase tourist visits to Desa Wisata Edukasi Cisaat Ciater.